Perancangan Media Pembelajaran Listrik Statis dan Dinamis Berbasis Android - Mahesi Agni Zaus; Rizky Ema Wulansari; Syaiful Islami; Doni Pernanda (INTECOMS: Journal of Information Technology and Computer Science, 2018)
This study discusses about design of static electricity and dynamic electricity learning media based on Android. designed learning media containing static and dynamic electrical materials that are abstract and not visible to see. The material is described in real and easily understood by learners. The method used in the design of learning media is SDLC (System Development Life Cycle) Waterfall model. And the design model of learning media using UML (Unified Modeling Language) with Use case diagram, flowchart and then developed using Adobe Flash CS6 tool. The results of this study indicate that the learning tool of static and dynamic electricity based on android easy to use for learners and teachers in the learning process. Keywords : Learning Tools, Android, Static Electricity, Dynamic Electricity